Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan di Warung Dua Umalas - Ni Luh Shindy Suardana; I Putu Bagus Suthanaya (Journal Research of Management, 2024)
Employees require a reference point for the leadership's involvement in managing employee discipline in order to be aware of how to follow the company's policies. A high level of rule and regulatory awareness among employees will increase motivation at work and performance. The study's goal is to ascertain how pay and workplace rules affect employees' performance at Warung Dua Umalas. A descriptive research method with a quantitative approach is applied in this study. Employee performance (Y) is positively influenced by the Compensation Variable (X1) by a factor of 2,190, meaning that for every unit rise in the Compensation Variable (X1), there is a 2,190 unit increase in employee performance (Y). When the work discipline variable (X2) is increased by one unit, employee performance (Y) rises by 2.622 units, indicating that the work discipline variable has a positive influence on work discipline of 2.622. The employee performance (Y) at Warung Dua Umalas is partially positively and significantly impacted by the outcomes of the compensation test (X1) results. The performance of Warung Dua Umalas employees (Y) is significantly and partially impacted by the test findings of the work discipline variable (X2). The organization should pay attention to compensation and work discipline together because they can greatly increase employee performance at Warung Dua Umalas. Compensation and work discipline play a key role in enhancing employee performance